1992
DOI: 10.1002/pssb.2221720215
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen in InxGa1−xAsyP1–y Grown on GaAs

Abstract: The measurement of DLTS on the alloy In,Ga,-,As,P,-, (0 5 y 5 0.3; 0.5 2 x 2 0.35) shows a new signal, labeled as E,, with an activation energy of E, -0.61 eV and the SIMS signals show a large number of oxygen. To clarify is further, the energy of the deep level E , is quantitatively calculated by using Vogl's tight-binding theory and Hjalmarson's deep level theory. As a result, the deep A,-symmetric level associated with an oxygen on the anion site of In,Gal-,As,P,-, locates deeply in the band gap. Thus, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
1997
1997

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…They examined the chemical trends for a wide variety of substitutional defects, and found good agreement with available data. Zhu et al (1992) used tight-binding to confirm the identification of a deep-level trap. They found that oxygen in In x Ga 1−x As y P 1−y grown on GaAs gives a new level, which has been identified as an anion-site defect.…”
Section: Defects and Dislocationsmentioning
confidence: 99%
“…They examined the chemical trends for a wide variety of substitutional defects, and found good agreement with available data. Zhu et al (1992) used tight-binding to confirm the identification of a deep-level trap. They found that oxygen in In x Ga 1−x As y P 1−y grown on GaAs gives a new level, which has been identified as an anion-site defect.…”
Section: Defects and Dislocationsmentioning
confidence: 99%